2011
DOI: 10.1097/mao.0b013e3182138fc5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Quality of Life and Audiometric Test Outcomes in Vestibular Schwannoma Patients Treated With Gamma Knife Surgery

Abstract: No significant decline in global QOL occurred after GKS with relatively short follow-up and approximately 50% survey completion. When discussing therapy options with VS patients, anticipated treatment-related QOL outcomes should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…As suggested from published series, local control is comparable after both treatments; regarding hearing preservation, especially dose in SRS has a significant impact in patients presenting with useful hearing prior to treatment. With doses of 13 Gy or lower, however, hearing preservation is comparable after both groups, in line with large series reported previously [3,6,7,11,12,[14][15][16][17][18][19][20][21][22][23][25][26][27][28][29][30]33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. With higher doses above 13 Gy, the risk for treatment-related side effect especially to the cranial nerves increases significantly; on the other hand, no benefit has been shown for higher dose with respect to local control [12,13,28,36].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As suggested from published series, local control is comparable after both treatments; regarding hearing preservation, especially dose in SRS has a significant impact in patients presenting with useful hearing prior to treatment. With doses of 13 Gy or lower, however, hearing preservation is comparable after both groups, in line with large series reported previously [3,6,7,11,12,[14][15][16][17][18][19][20][21][22][23][25][26][27][28][29][30]33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. With higher doses above 13 Gy, the risk for treatment-related side effect especially to the cranial nerves increases significantly; on the other hand, no benefit has been shown for higher dose with respect to local control [12,13,28,36].…”
Section: Discussionsupporting
confidence: 90%
“…Usually hearing reduction developed directly after surgery, hearing deterioration after radiotherapy usually gradually develops over time during follow-up. Depending on the series on FSRT or SRS, hearing preservation rates range between 30% and 98% [16,20,28,29,39,47,48,55]. Several factors influence hearing preservation, such as dose, fractionation or patient-individual factors; additionally, it has been shown that patients with superior hearing function, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…35,37 Gamma Knife radiosurgery SF-36 No significant decline in SF-36 results were noticed after Gamma Knife radiosurgery. 38 QOL did not differ significantly between conservative management and Gamma Knife radiosurgery. 31 Chordoma 17…”
Section: Sf-36mentioning
confidence: 77%
“…Radiation of VS has gained popularity [24,32], largely from reported success in arresting tumor growth without long-term sequelae and improved quality of life [29,[33][34][35]. Stereotactic radiation may be delivered in a single dose, termed fractionated stereotactic radiosurgery or in fractions, termed stereotactic radiotherapy.…”
Section: Stereotactic Radiationmentioning
confidence: 99%